2015
DOI: 10.3389/fpls.2015.00198
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing, de novo assembly and comparative analysis of Raphanus sativus transcriptome

Abstract: Raphanus sativus is an important Brassicaceae plant and also an edible vegetable with great economic value. However, currently there is not enough transcriptome information of R. sativus tissues, which impedes further functional genomics research on R. sativus. In this study, RNA-seq technology was employed to characterize the transcriptome of leaf tissues. Approximately 70 million clean pair-end reads were obtained and used for de novo assembly by Trinity program, which generated 68,086 unigenes with an avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…From 40 to 71 million reads were generated per samples (100 bp, paired-end), representing 11 × coverage of the radish genome. Previous studies reported approximately 70,000 unigenes in radish (Wang et al, 2013a,b; Wu et al, 2015). Consistent with this, our transcriptome analysis identified 71,188 genes despite using only shoot tissue for the RNA-Seq analysis.…”
Section: Discussionmentioning
confidence: 96%
“…From 40 to 71 million reads were generated per samples (100 bp, paired-end), representing 11 × coverage of the radish genome. Previous studies reported approximately 70,000 unigenes in radish (Wang et al, 2013a,b; Wu et al, 2015). Consistent with this, our transcriptome analysis identified 71,188 genes despite using only shoot tissue for the RNA-Seq analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Glucoraphasatin is the predominant GSL in the root and accounts for more than 90% of the total GSLs present in Japanese cultivars (Ishida et al, 2012). Recently, the genome sequence and transcriptome profiles of radish have facilitated studies on the GSL biosynthetic pathway by profiling of GSL synthesis-associated genes of Arabidopsis (Wang et al, 2013;Kitashiba et al, 2014;Mitsui et al, 2015;Wu et al, 2015). However, because glucoraphasatin is characteristic of radish and not found in other Brassica spp., the pathway for its biosynthesis remains unclear.…”
mentioning
confidence: 99%
“…Adaptor and duplicate sequences and ambiguous and low-quality reads were removed, and high-quality reads for each cultivar were separately assembled using the NGS QC Toolkit v.2.3 [43] and a series of stringent criteria. After this quality control step, 60,348,338 high-quality reads with a length of 101 bp (average length: 86.62bp) were retained (Fig 1): these were used to assemble contigs and obtain transcripts in default parameter settings by the Trinity program [44]. In total, 41,002 contigs were generated with a k-mer of 25, which was pre-defined to avoid misassembly caused by a too-short k-mer while retaining a reasonable number of reads [45,46].…”
Section: Resultsmentioning
confidence: 99%